DEPENDENCE OF INPUT ENERGY FROM THE RIGIDITY OF THE FOUNDATION (Balkan Journal of Applied Mathematics and Informatics, 2022)
In this paper we studied the characteristics of the response when different boundary conditions are applied. We analyzed a two-dimensional model of the ground-foundation system (construction) and investigated how the physical-mechanical characteristics (density and propagation velocity) of the constituent elements of the ground-foundation system affect the energy that will enter the building.
Keywords: dependence; foundation; wave; energy